Kemampuan Membaca Siswa Kelas V SDN Inti Pengambangan 3 Banjarmasin - Niken Octaviyanti Dewi; Ida Komalasari; Noormaliah (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The ability to read is a requirement that must be met, so the ability to read must be trained. However, in reality, the reading ability of students is still low. This study aims to determine the reading ability and the factors that influence the reading ability of the fifth grade students of SDN Inti Pengambangan 3 Banjarmasin. This type of research is descriptive qualitative research. The subjects of this study were homeroom teachers and class Va students at SDN Inti Pengambangan 3 Banjarmasin. Data collection techniques used are interviews and documentation. The data analysis technique is done by word reduction, data presentation, and conclusion drawing. The results showed that 1) students' reading ability was included in the good category when reading, but there were three students who were not fluent in reading. 2) factors that affect students' reading ability are intellectual factors, state factors, and factors from the child himself.